Bunker Oksigen Dan Karbon (Bok) Di Lingkungan Sekolah Sebagai Penyimpan Karbon, Manfaat, Dan Nilai Ekonominya - Suyadi Suyadi; Venny Handayani; Agustina Fina; Wira Sudirja (BERITA BIOLOGI, 2021)
The impacts of pollution and climate change occurred in global and local communities, including at school environment. Uncomfortable school environment due to pollution and school damage due to sea-level rise interferes with learning processes and reduces students' academic performance. A new approach of a school greening programme called Bunkers of Oxygen and Carbon (BOCs) was developed in a public school (SMA Negeri 3 Merauke) in Merauke, Papua using a thematic approach to mitigate pollution and climate change. The research showed that carbon storage of BOCs is mean 74 Mg ha-1 . This is equal with carbon dioxide equivalent (CO2e) of mean 271 Mg CO2e ha-1. The capacity of BOCs as carbon storage can be optimized due to the age of vegetation in BOCs is only four years old, and below ground carbon stock was measured only up to 50 cm depth. The amount of carbon stock in BOCs was influenced by vegetation health (tree density and canopy coverage) and vegetation structure (tree diameter and height) in the BOCs (r2 = 0.56, p = 0.001). The mean economic value of carbon stocks in the BOCs was US $ 189 billion ha-1. This economic value may underestimate as many benefits and functions of the BOCs were excluded from the calculation. BOCs have ecological functions as a habitat for many wildlife species, various ecosystem services, recreational areas, aesthetic values, oxygen supply, and a place to improve creativity and as natural laboratories for practice and learning from nature. Therefore, the development of BOCs in the school environment across Indonesia is important as the functions and benefits are crucial to mitigate pollution and climate change, improve the learning process and the quality of national education.